1997
DOI: 10.1128/jvi.71.5.3466-3473.1997
|View full text |Cite
|
Sign up to set email alerts
|

RNA-protein interactions: involvement of NS3, NS5, and 3' noncoding regions of Japanese encephalitis virus genomic RNA

Abstract: The mechanism of replication of the flavivirus Japanese encephalitis virus (JEV) is not well known. The structures at the 3 end of the viral genome are highly conserved among divergent flaviviruses, suggesting that they may function as cis-acting signals for RNA replication and, as such, might specifically bind to cellular or viral proteins. UV cross-linking experiments were performed to identify the proteins that bind with the JEV plus-strand 3 noncoding region (NCR). Two proteins, p71 and p110, from JEV-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 64 publications
(95 reference statements)
4
77
1
2
Order By: Relevance
“…By using GST-pulldown and coimmunoprecipitation, we demonstrated that DDX5 can interact with JEV core, NS3, NS5-MTase and NS5-RdRp, suggesting that DDX5 might act as a cofactor for JEV proteins in virus replication. It has been suggested that cellular proteins can bind to viral 5 0 and/or 3 0 UTR to modulate viral translation and/or replication (Chen et al, 1997). Our studies showed that DDX5 can only interact with viral 3 0 UTR and colocalize with viral RNA.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…By using GST-pulldown and coimmunoprecipitation, we demonstrated that DDX5 can interact with JEV core, NS3, NS5-MTase and NS5-RdRp, suggesting that DDX5 might act as a cofactor for JEV proteins in virus replication. It has been suggested that cellular proteins can bind to viral 5 0 and/or 3 0 UTR to modulate viral translation and/or replication (Chen et al, 1997). Our studies showed that DDX5 can only interact with viral 3 0 UTR and colocalize with viral RNA.…”
Section: Discussionmentioning
confidence: 49%
“…It has been shown JEV core, NS3 and NS5 proteins play important roles in viral genome replication (Chen et al, 1997;Uchil and Satchidanandam, 2003a). By using GST-pulldown and coimmunoprecipitation, we demonstrated that DDX5 can interact with JEV core, NS3, NS5-MTase and NS5-RdRp, suggesting that DDX5 might act as a cofactor for JEV proteins in virus replication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The viral replication is initiated by the replication complex through a process of RNA-dependent RNA polymerization in the perinuclear endoplasmic reticulum membranes (Westaway et al, 2003). Nonstructural proteins 3 and 5 are components of the replication complex, which associates with the 3′ noncoding region of genomic RNA to initiate viral replication (Chen et al, 1997;Edward and Takegami, 1993). NS5, the largest and most conserved viral protein, contains methyltransferase (MTase) and RNA-dependent RNA polymerase (RdRp) domain.…”
Section: Introductionmentioning
confidence: 99%